2022
DOI: 10.1101/2022.01.19.476937
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visualizing Synaptic Dopamine Efflux with a 2D Nanofilm

Abstract: Chemical neurotransmission constitutes one of the fundamental modalities of communication between neurons. Monitoring release of these chemicals has traditionally been difficult to carry out at spatial and temporal scales relevant to neuron function. To understand chemical neurotransmission more fully, we need to improve the spatial and temporal resolutions of measurements for neurotransmitter release. To address this, we engineered a chemi-sensitive, two-dimensional nanofilm that facilitates subcellular visua… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Recent work shows that the dopaminergic SNr dendrites contain the mRNA necessary for local translation of dopamine transmission machinery ( Hobson et al, 2022 ). Another recent study using dopamine-sensitive nanofilm and cultured dopaminergic neurons observed that some dopaminergic dendrites released dopamine, while others did not ( Bulumulla et al, 2022 ). Because dendrodendritic communication between dopaminergic neurons depends on dopamine transporters, but does not depend strongly on dopamine diffusion ( Ford et al, 2010 ; Condon et al, 2021 ), the D2 dopamine receptors activated by somatodendritic release of dopamine must be in close proximity to the release sites.…”
Section: Potential Importance Of the Bouquet Structurementioning
confidence: 99%
“…Recent work shows that the dopaminergic SNr dendrites contain the mRNA necessary for local translation of dopamine transmission machinery ( Hobson et al, 2022 ). Another recent study using dopamine-sensitive nanofilm and cultured dopaminergic neurons observed that some dopaminergic dendrites released dopamine, while others did not ( Bulumulla et al, 2022 ). Because dendrodendritic communication between dopaminergic neurons depends on dopamine transporters, but does not depend strongly on dopamine diffusion ( Ford et al, 2010 ; Condon et al, 2021 ), the D2 dopamine receptors activated by somatodendritic release of dopamine must be in close proximity to the release sites.…”
Section: Potential Importance Of the Bouquet Structurementioning
confidence: 99%
“…Single-walled carbon nanotubes (SWCNTs) benefit from unique optical and electronic properties, which render them favorable fluorescent probes for imaging, sensing, and biomedical applications, owing to their fluorescence in the near-IR range where tissue, blood, and biological samples in general are mostly transparent. Moreover, SWCNT sensors are stable at room temperature, provide spatiotemporal information, and do not photobleach upon use, unlike many other fluorescent sensors. The mechanism of SWCNT-based sensors usually relies on tailored functionalization of the nanotube surface, which mediates the interaction with the analyte of interest, such that binding of the target molecule results in a modulation of the emitted fluorescence. Fluorescent SWCNT sensors were applied for the biosensing of different analytes and enzymes. ,,,, These range from monitoring progesterone and cortisol in vivo (mice), fibrinogen and insulin in blood and cell culture, , nitroaromatics and pathogens , in vivo (plants), volatiles in the gaseous phase, to enzymatic activity. …”
Section: Introductionmentioning
confidence: 99%
“…In particular, SWCNTs emit bright fluorescence in the nIR range (900-1400 nm), which does not photobleach nor blink. [17] Moreover, given proper functionalization, they are highly biocompatible, [18,19] and were successfully utilized as imaging and sensing probes in various applications such as within plants, [14,20] live cells, [21,22] animals, [23][24][25] and brain tissue, [26,27] for example, the brain extracellular space (ECS). [28] For sensing, functionalized SWCNTs can bind specific analytes such as proteins, small molecules, metal ions, or bacteria, and exhibit fluorescence modulations upon interaction, whereas for imaging, they can be easily tracked in complex biological environment owing to their nIR fluorescence.…”
Section: Introductionmentioning
confidence: 99%